Collingwood, Winch and Wittgenstein on the Status of Logic - Lagerspetz, Olli; Ahlskog, Jonas (Austrian Ludwig Wittgenstein Society, 2022)
This paper compares R. G. Collingwood and Peter Winch, with Wittgenstein as an important background figure. Their shared philosophical concerns were (1) resistance to ontology, especially metaphysical realism, in favour of a view on philosophy as cultural self-understanding; and (2) critique of the idea of logic as a formal science, labelled “Aristotelian Logic”. Instead, they advanced a conception of logic as the contextually sensitive analysis of actual reasoning. The connection between these two concerns was particularly explicit in Collingwood’s work. We bring out the connection via their reactions to Moore’s “Proof of an External World”. The meaning of what Moore says is indeterminate, because he has not specified the doubt to which his “Proof” is an answer. We see the logical status of a statement when we understand how it constitutes an answer to a question that has arisen. As Collingwood would put it, the logical analysis of a concrete piece of reasoning is an ‘historical’ exercise.